Composable information flow verification for service chain based on model checking - Ning XI; Jian-feng MA; Cong SUN; Di LU; Tao ZHANG (Tongxin xuebao)
A composable information verification approach is proposed for the secure service chain composition.Based on the secure service component，the security constraints for the component’s composibility is specified and the information flow verification algorithms is proposed.Through the experiments and simulation，it shows that the approach can decrease the verification cost effectively and improve the efficiency of the verification.